Impact of a Pluridisciplinary Protocol of Respiratory Physiotherapy and Active Music Therapy on Anxiety, Depression and Pain on Lung Post-Transplant Patients (PPRPAM). Issue 1 (2022) - lopez, Jesus Calabuig; Melis, Martine; Vignaux, Claire Merveilleux des; Chatron, Eva; Rea, Aurelie; Regnier, Mederic; Derrien, Nadege; Varillon, Yvonne; Cottin, Vincent; Mornex, Jean-François
No abstract available